Regional Innovation Ecosystems Fostering Sustainable Development - Takala, Minna; Tukiainen, Taina (AHFE International, 2022)
Since 2014, European Union has recommended European regions to conduct development activities based on Smart Specialisation. Smart Specialisation is a place-based approach characterised by the identification of strategic areas based both on the analysis of the regional strengths and potential of the economy. It aims to enhance prosperity of European regions by creating enabling conditions, accelerating research, development and innovation activities as well as supporting Entrepreneurial Discovery Process (EDP) with wide stakeholder involvement. This outward-looking approach embraces open innovation ecosystems supported by collaborative activities combined with effective monitoring mechanisms. This paper examines experiences of the creation and implementation of smart specialisation strategies across Baltic Sea Region and at Häme Region in Finland. The paper introduces results of a SmartUp BSR –project. The study builds on ten cases in nine countries of the Baltic Sea Region. Large number of regional stakeholders involved in regional smart specialization strategy processes participated in project events to share their experiences and best practices. The aim was also to encourage participants to include Sustainable Development Goals 2030 into regional development activities. Activities also included innovation camps and pilots, which endorsed and accelerated activities related to strategy content and chosen spearheads. This also enhanced stakeholder participation and international collaboration widening the scope of the innovation ecosystem. The paper takes a deeper look as a case example of Häme Region, Finland. At Häme region open regional portfolio management tools were created, piloted and taken in use to support implementation of regional smart specialization strategy. Prior to development a benchmarking study was conducted with 18 Finnish regions. The aim was to support collaboration among regional stakeholders, provide flexible monitoring and reporting practices over the time and collection of new development ideas for the future. Experiences of new portfolio management tool practices were openly shared with other Finnish regions and interested stakeholders.The goal of this paper is to share experiences from ecosystem based leadership and management practices for regional development to support active stakeholder participation stakeholder and sustainable development.
Keywords: Innovation camps; Innovation ecosystem; participation; Portfolio management; smart specialization; sustainability; regional development; fi=Henkilöstöjohtaminen|en=Human Resource Management|